Variasi Nilai Tegangan Percik Arrester Akibat Pengaruh Kapasitas Trafo Daya dan Jarak Arrester - Oktaviani, Wiwin A; Septiaji, Rahmat; Taufik, Barlian (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2022)
The ability of each substation to withstand lightning and overvoltage affects the power distribution of the power system. In order to make the best operation of the substations, it is necessary to install Arresters which are used to protect the transformers in each substation from overvoltage caused by lightning surges. In this study, the effect of capacity on the placement distance of the arrester is discussed with 30 MVA and 60 MVA transformers. The purpose of this study was to determine the effect of the power transformer capacity of the four substations on the value of the arrester spark voltage and to obtain the optimal arrester installation technique at each substation using the Lagrange optimization method. Lagrange optimization method is used to determine the optimal distance between the arrester and the power transformer. The calculation results show that in a transformer with a capacity of 60 MVA, the Arrester spark voltage occurs at t = 20 microseconds with a voltage drop of 390.49 kV. Meanwhile, in a transformer with a capacity of 30 MVA, the Arrester spark time is at t = 13.9 microseconds with a voltage drop of 266.3 kV. This shows the capacity of the transformer that affects the magnitude of the Arrester's spark voltage and the spark time. Thus, the smaller the transformer capacity, the smaller the arrester spark time with the large voltage drop